Perancangan dan Perbaikan Dokumen Mutu Departemen PPIC di PT Astra Otoparts Divisi Adiwira Plastik - Martin Agusta; Tanti Octavia (Jurnal Titra, 2013)
Quality Document for PPIC Department (business process, standard operating procedure, work instruction and supporting document) was last updated in 2003, so it does not fit anymore. This condition causes high variation of work, obtructs the application of Toyota Production Sustem and ISO 9001. This problem can be solved by designing the new quality document. Results obtained 17 existing WI deleted, 6 existing  SOP revised, 31 existing WI revised, 2 proposed SOP and 130 proposed  WI added. Business process, supporting documents (form and standard) and tools are also improved in order to support the new quality document. Lastly, controlling system is designed to ensure that quality document always fits with actual condition.